EDUKASI DAN SOSIALISASI PEMANFAATAN DAUN TEH HIJAU (Camellia sinensis L) DALAM MENGURANGI RESIKO PENYAKIT HATI - Ani Riyani; Nani Kurnaen (Poltekkes Kemenkes Bandung, 2022)
Liver disease can be caused by infectious substances, pollutants, free radicals, toxic foods, drugs and chemical compounds. Research has been carried out on the effect of green tea leaf ethanol extract in protecting the liver of Balb/C strain mice from CCl4 induction, with the result that green tea leaf extract can protect liver cells from damage. Green tea leaves contain compounds that function as antioxidants, anti-bacterial and hepatoprotectors so that they can be useful in maintaining liver health. This community service aims to provide education and socialization about the benefits of green tea leaves in protecting liver health to residents. Education includes explanations about liver disease, its causes and modes of transmission and how to prevent it. Education and socialization about the benefits of green tea leaves and how to consume them. Evaluation is done by checking blood pressure and questionnaires on the knowledge that has been given. A total of 40 residents have participated in community service, with the following results, the highest age is 41-50 years (42.5%), a decrease in blood pressure of 11% from 150/91 to 133/88, an increase in the percentage of knowledge about green tea after education and socialization from 55% to 69% and increased knowledge of liver and liver disease after education and socialization from 45% to 71%. The conclusion of this community service is that there are 40 people who participate in the community, aged around 20-83 years, a decrease in the blood pressure of residents, after consuming steeped green tea leaves, there is an increase in people's knowledge after socialization and education about green tea and how to consume the leaves have been carried out. green tea and increasing public knowledge after socialization and education about liver and liver disease were carried out